Pengaruh Kunjungan Wisatawan, Jumlah Objek Wisata, dan Lama Menginap dalam Pengembangan Ekonomi Lokal Provinsi Bali - Ni Putu Kumara Shanti; Nasikh (SAFE-Network, 2023)
The aim of this study is to analyze the impact of tourist visits, number of tourist attractions, and the average tourists stay time on Bali local original income (PAD). The study conducted in Bali, which includes nine districts/cities within it. The data applied in this research is secondary data which including data on the number of tourist visits, number of tourist objects, and the average length of stay of tourists in all districts/cities in Bali Province for the 2018-2022 period. The method of analytical used is panel data regression analysis with testing equipment in the form of Eviews software. Panel data regression analysis is a development of linear multiple regression which aims to determine significant factors based on repeated observations of an object at different times. According to the analysis that has been carried out, this research states that the number of tourist visits, the number of tourist attractions, and the average length of stay of tourists have a positive and significant effect on.